2016
DOI: 10.3934/publichealth.2016.4.891
|View full text |Cite
|
Sign up to set email alerts
|

Barriers of Female Breast, Colorectal, and Cervical Cancer Screening Among American Indians—Where to Intervene?

Abstract: Female breast, colorectal, and cervical cancer are three common cancers among people in the United States. Both their incidence and mortality rates can be dramatically reduced if effective prevention and intervention programs are developed and implemented, because these cancers are preventable through regular screenings. American Indians in the United States especially in the Northern Plains have a disproportionally high burden of these cancers. As a hard-to-reach population group, less attention has been paid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In South Dakota, results from the Behavioral Risk Factor Surveillance System 2010 revealed that 63.9% (n = 375) of American Indian participants aged 50 or older have never had a sigmoidoscopy or colonoscopy, compared with only 32.2% (n = 3,936) of white counterparts . In a preliminary study based on a community survey including 200 American Indians that aimed to identify other barriers to cancer care among American Indians in South Dakota, about 44% (n = 199) of participants had annual household income less than $25,000 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Dakota, results from the Behavioral Risk Factor Surveillance System 2010 revealed that 63.9% (n = 375) of American Indian participants aged 50 or older have never had a sigmoidoscopy or colonoscopy, compared with only 32.2% (n = 3,936) of white counterparts . In a preliminary study based on a community survey including 200 American Indians that aimed to identify other barriers to cancer care among American Indians in South Dakota, about 44% (n = 199) of participants had annual household income less than $25,000 …”
Section: Discussionmentioning
confidence: 99%
“…Other factors such as insurance coverage, socioeconomic factors, culture, knowledge about cancer, as well as degree of satisfaction with health professionals might also impact health care access. In the community survey conducted in a preliminary study, about 70% of the American Indians (n = 199) resided within 30 miles of health care services, but their cancer screening behaviors had been discouraged due to nonspatial factors, including no vehicles, high gas prices, no health insurance, no regular health care provider, and lack of encouragement for cancer screening by health professionals. Results from the present study revealed that most areas were within 30 min of a CRC screening facility and thus gaps in the spatial accessibility might be small in South Dakota.…”
Section: Discussionmentioning
confidence: 99%
“…The NBCCEDP may play an important role in supporting screening, 31 as Alharbi et al reported similar results and demonstrate that low‐income people with Medicaid were less likely to receive preventative services like pap tests, suggesting there might be something about Medicaid itself that provides a barrier to screening. BRFSS estimates guideline‐adherent screening to be 65%–80% among AIAN and White people, depending on the year, which may be too high to see gains from increased insurance coverage, particularly if coverage does not overcome other barriers to screening like access to transportation, distance to services, childcare coordination, or availability of healthcare, etc 32–34 . There are also ways that the Medicaid expansions may ultimately work to decrease cervical cancer related morbidity and mortality, which we were unable to examine.…”
Section: Discussionmentioning
confidence: 96%
“…Geography, spatial configuration, and mobility are examples, as seen in a patient’s “ability to seek” [ 22 ]. Travel time has been identified as a strong predictor of satisfaction with accessibility and associated with opportunity cost for service use [ 24 , 30 ].…”
Section: Introductionmentioning
confidence: 99%